(untitled) (diségno, 2017)
From 1967, when Gaspare De Fiore published La figurazione dello spazio architettonico, to the present day, exactly 50 years have gone by, yet the work retains the same freshness I discovered when I started reading it, for the first time, during our academic education. Perhaps the secret is to be found in the ultimate spirit of the book, which, as the author states in the introduction: “[...] wants to be just a research proposal of this ‘sense of space’”